A high voltage solid state symmetric supercapacitor based on graphene–polyoxometalate hybrid electrodes with a hydroquinone doped hybrid gel-electrolyte. Issue 46 (28th October 2015) - Dubal, Deepak P.; Suarez-Guevara, Jullieth; Tonti, Dino; Enciso, Eduardo; Gomez-Romero, Pedro
Abstract : Development of high energy density hybrid electrode based on rGO–PMo12 for all-solid state supercapacitors along with actual demonstration of lighting of thirty one LEDs (NEO). Abstract : In pursuit of high capacitance and high energy density storage devices, hybrid materials have quickly garnered well-deserved attention based on their power to merge complementary components and properties. Here, we report the fabrication of all-solid state symmetric supercapacitors (ASSSC) based on a double hybrid approach combining a hybrid electrode (reduced graphene oxide–phoshomolybdate, rGO–PMo12 ) and a hybrid electrolyte (hydroquinone doped gel-electrolyte). To begin with, a high-performance hybrid electrode based on H3 PMo12 O40 nanodots anchored onto rGO was prepared (rGO–PMo12 ). Later, an all-solid state symmetric cell based on these rGO–PMo12 electrodes, and making use of a polymer gel-electrolyte was assembled. This symmetric cell showed a significant improvement in cell performance. Indeed, it allowed for an extended potential window by 0.3 V that led to an energy density of 1.07 mW h cm −3 . Finally, we combined these hybrid electrodes with a hybrid electrolyte incorporating an electroactive species. This is the first proof-of-design where a redox-active solid-state gel-electrolyte is applied to rGO–PMo12 hybrid supercapacitors to accomplish a significant enhancement in the capacitance. Strikingly, a further excellent increase in the device performance (energy density of 1.7 mW h cm −3 ) was realized with the hybrid electrode–hybrid electrolyte combination cell as compared to that of the conventional electrolyte cell. Thus, this unique symmetric device outclasses the high-voltage asymmetric counterparts under the same power and represents a noteworthy advance towards high energy density supercapacitors.